Literary Ecology Study of Novels: A Strategy for Instilling Environmental-Based Character Education Values - Evia Firnadia; Nurizzati Nurizzati (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to describe the attitude of avoiding the nature of damaging the environment, fostering an attitude of caring and responsible for the environment, and the attitude of saving the environment contained in the novel Serdadu Pantai by Laode Insan and the novel Dari Rahim Ombak by Tison Sahabuddin Bungin. The research method used is a qualitative descriptive research method, with the research stages of the preparation stage, the field stage, and the data analysis stage. The data in this study are in the form of words, phrases, and sentences related to literary ecology. The data sources of this research are the novel Serdadu Pantai by Laode Insan and the novel Dari Rahim Ombak by Tison Sahabuddin Bungin. Data collection techniques used reading and note-taking techniques. Based on the results of data analysis and discussion, it is known that the novel Serdadu Pantai dan Dari Rahim Ombak emphasizes to the reader how important it is to have a character who cares about the environment, so that humans can live in harmony with nature. In both novels, there is a great message to the readers about how fatal the impact that will be received by humans if they live by destroying the environment.